COMPLAINT STRATEGY OF EFL LEARNERS FROM THE PERSPECTIVE OF DISCOURSE COMPLETION TASK (A CASE STUDY OF STUDENTS OF ENGLISH DEPARTMENT UNIVERSITAS BRAWIJAYA) - FATMASARI, DIAH RINI (Jurnal Ilmiah Mahasiswa FIB, 2015)
Key words: Complaint Strategies, Students of English Department UniversitasBrawijaya, Discourse Completion TaskThis study focuses on identifying the complaint strategies used by Students of English Department Universitas Brawijaya in fifth semester by using theory from Trosborg (1995) and. This study was conducted in order to find out the types of complaint strategies used by them and to know how social status influences their realization of complaint. The problems of this study are (1) What are the types of complaint strategies used by students of English Department Universitas Brawijaya and (2) How does the social status influence the students’ realization of complaint strategy.This study used qualitative approach because the analysis was the form of description rather than number. The data were the utterances containing complaint produced by students of English Department Universitas Brawijaya in fifth semester and the data sources were 30 Students of English Department Universitas Brawijaya in fifth semester. The data were collected by using several steps; designing the instrument of Discourse Completion Task, making the prompts situation in academic setting and giving the questionnaire to the participants.This study revealed that there were four categories of complaint and seven sub-strategies of complaint. Those were three Hints in category No Explicit Reproach, one Annoyance and three Ill Consequences in category Disapproval, 14 Indirect Accusations and 29 Direct Accusations in category Accusation, three Modified Blames and seven Modified Blames (Behavior) in category Blame. Strategy of Modified Blame (Person) was not found in this study. The writer also found that social status influences the degree of politeness of the students. In this study, the students use Indirect Accusation when the complainee has higher social status. Moreover, when the complainee has equal social status they tend to use Direct Accusation as the major strategy.For the next researchers, the writer suggest them use another approach in order to analyze speech act of complaint and better to compare the study of complaint between native speaker of English and EFL Learners.